Performance Analysis of a Vlc System Applied to a Hospital Environment for Iot-Based Smart Patient Monitoring - Soto-Gomez, J (Institute of Electrical and Electronics Engineers Inc., 2024)
This article investigate the deployment of effective communication networks for smart IoT-based smart patient monitoring in medical facilities, advocating for the adoption of Visible Light Communication (VLC) technology. Initially, the physical scenario is analyzed, taking into account factors such as line-of-sight (LOS) and nonline-of-sight (NLOS) channel components. Furthermore, a transmitter is designed to offer a substitute in the event of potential interruptions due to patient motion or loss of line-of-sight elements. The performance of the proposed system is verified under certain performance metrics, such as the Channel Impulse Response (CIR) and the Cumulative Distribution Function (CDF), with respect to power measurements at different points. The results highlight the effects that NLOS rays have on the received data and the received power. Therefore, this study serves as a step towards the development of more sophisticated systems for patient monitoring using enabling technologies such as VLC. © 2024 IEEE.